SURAT KABAR SEBAGAI MEDIA DAKWAH - Masmuddin Masmuddin (AL TAJDID, 2009)
Dawah in Islam is an absolute obligation executed by every moslem according to ability owned. Therefore method of forwarding of dawah is very important matter, because can determine its effectivity, so that present day dawah have ought to be tidy in so many effective method as according to its object condition.Present day dawah through mass media/newspaper is a step in the right direction, because with the mass media of dawah object will be more quickly accept the information needed. Way of communicating in the form of dawah through mass media have to follow the press theory without leaving values of religion teaching, in order dawah messages can be receive by its target.